Media Accessibility of Taboo in Arabic: The Analysis of a Political Film - Jimenez-Andres, Maria; El Taweel, Ghanimeh; Hejazi, Naya (Journal of Audiovisual Translation, 2025)
Research and practice on subtitling for the Deaf and Hard-of-Hearing (SDH), Audio description (AD) in Arabic, and Arabic Sign Language (ArSL) remain scant, with only a few studies conducted to date and an equally low number of titles with Arabic AD and SDH available on on-demand platforms. Language professionals in the Arabic-speaking world often face challenges in adapting international standards or guidelines to meet the unique linguistic and cultural needs of Arabic-speaking audiences, so more research is needed with a variety of audiences to understand user preferences and expectations. This article investigates the accessibility of taboo in Arabic, SDH, AD, and ArSL, drawing from the AD, ArSL, and SDH in Arabic and English developed by students in the Master’s in Audiovisual Translation program at Hamad bin Khalifa University for a film screened at a festival in Qatar in November 2023. The film, 200 Meters, set in occupied Palestine, contains taboo language that needed to be mediated, especially given the conservative nature of the Qatari society. Likewise, the film’s political nature compelled subtitlers and describers to make choices that inevitably reveal a certain political stance. This article explores the choices made for the subtitles, sign language interpretation, and audio description of the film, and their implications, reflecting on the fact that SDH and AD can be a political act. It is hoped that this study will serve as a basis for further research in Arabic AD and as a contribution to the development of guidelines for Arabic AD. Lay summary This article looks at how films are made accessible to people who Deaf or hard of hearing, and those who are blind or partially blind in Arabic-speaking countries. This includes subtitles for Deaf and Hard-of-hearing audiences, audio descriptions (where a narrator explains what's happening in the film), and sign language. There isn't much research on this in Arabic yet, and very few films with these features are available to watch online. The article focuses on a film called 200 Meters made by Ameen Nayfeh, which was shown at a festival in Qatar in 2023. The film is set in Palestine. 200 Meters has some sensitive and politically charged language that needed special attention when making it accessible to different audiences. Since Qatar is a conservative country, the translators had to be careful about how they handled these sensitive topics in subtitles, sign language, and audio descriptions. The study shows that making these features can also be a way to express political ideas. The authors hope that this research will help improve the way films are made accessible to Arabic-speaking audiences and encourage more work in this area.